Basic equine veterinary clinical skills guidelines - Khairuddin, Nurul Hayah (Universiti Putra Malaysia Press, 2019)
Basic Equine Veterinary Clinical Skills Guidelines, a valuable learning tool for veterinary students, as well as other students in the animal husbandry or animal health care related field of studies. Standardised clinical skills are clearly explained with aid of photographs so students could follow and practice the given guidelines of the most basic equine veterinary clinical practice that routinely performed by equine veterinary practitioners. Nurul Hayah Khairuddin (N.H. Khairuddin) joined the Department of Veterinary Clinical Studies, Universiti Putra Malaysia in November 2011 as a Senior Lecturer. She received her PhD in Veterinary Clinical Studies from University of Glasgow, United Kingdom in 2011. Prior to that, she received her Doctor of Veterinary Medicine in 2007, and Diploma of Animal Health and Husbandry in 2002 from Universiti Putra Malaysia. In 2012, she was absorbed to the Department of Farm and Exotic Animal Medicine and Surgery to support the clinical side of the faculty at the University Veterinary Hospital (UVH), Faculty of Veterinary Medicine, UPM. Currently, Nurul Hayah is the Head of Department at the same department.